2013
DOI: 10.1007/s00204-013-1116-3
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to multi-walled carbon nanotubes results in aggravation of airway inflammation and remodeling and in increased production of epithelium-derived innate cytokines in a mouse model of asthma

Abstract: With the development of nanotechnologies, the potential adverse effects of nanomaterials such as multi-walled carbon nanotubes (MWCNT) on the respiratory tract of asthmatics are questioned. Furthermore, investigations are necessary to understand how these effects might arise. In the present study, we hypothesized that epithelium-derived innate cytokines that are considered as important promoting factors in allergy may contribute to an aggravating effect of MWCNT on asthma. We investigated in the mouse the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 56 publications
4
43
0
Order By: Relevance
“…25 In particular, oxidative stress has been proposed as the possible underlying mechanism by which CNTs exacerbate asthma in animal studies. 22,23,50 Indeed, the observed oxidative stress response was more pronounced in asthmatic tissues, thus further supporting the in vivo observations. Analysis of -the IL-8 expression, a critical airway epithelialderived (pro-)inflammatory chemokine primarily implicated in acute inflammation and accumulation of neutrophils in inflammatory diseases, 51 revealed an increase in both healthy and asthmatic MWCNT-exposed cells (Figure 6a).…”
Section: Resultssupporting
confidence: 83%
“…25 In particular, oxidative stress has been proposed as the possible underlying mechanism by which CNTs exacerbate asthma in animal studies. 22,23,50 Indeed, the observed oxidative stress response was more pronounced in asthmatic tissues, thus further supporting the in vivo observations. Analysis of -the IL-8 expression, a critical airway epithelialderived (pro-)inflammatory chemokine primarily implicated in acute inflammation and accumulation of neutrophils in inflammatory diseases, 51 revealed an increase in both healthy and asthmatic MWCNT-exposed cells (Figure 6a).…”
Section: Resultssupporting
confidence: 83%
“…Further, JAG1 silencing inhibited the differentiation of Th2 cells and promoted the differentiation of Th1 cells. Consistent with the previous reports, JAG1 promoted Th2 differentiation on dendritic cells [23]. The Th1/Th2 balance plays an important role in the AHR.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that CNT fibers have adjuvant capacity as they aggravate allergen-induced airway inflammation [11-13,15,16]. Here, we investigated whether CNT have the ability to induce characteristics similar to allergic airway inflammation in healthy mice.…”
Section: Discussionmentioning
confidence: 98%